Aplikasi Pembelajaran Bahasa Jepang Hiragana, Katakana dan Kanji Dasar - Salahudin Robo; M. Riandi Widiyantoro; Ichsan Tambijo; T Trisno (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Japanese is the national language of Japan which is used by Japanese people in their daily activities. With the spread of Japan's influence throughout the world, including Indonesia, the number of Indonesian people interested in learning Japanese is second in the world based on a survey conducted by the Japan Foundation in 2015 and 2018. However, at one of the Japanese language education facilities in Indonesia, at SMKN 1 Pariwisata Jayapura, there are still students who have difficulty learning Japanese. This study aims to make it easier for Japanese language learners to learn the material more effectively and efficiently by applying it to Android-based learning media. The method used in this research is SWOT analysis as an analytical method, UML for design method, waterfall method as a system development method, and system testing method with black-box testing method and the user acceptance testing (UAT) method. This research produces an application that utilizes Android technology as an efficient means of learning Japanese because it can be accessed anytime, anywhere. And also with easy materials and practice questions can help students to understand the material more effectively